2017
DOI: 10.1002/rcm.7885
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of passive sampler collection for atmospheric NO2 isotopes under simulated environmental conditions

Abstract: Suitable conditions for passive sampler collection of NO isotopes are in environments ranging from 11 to 34 °C and 1 to 78% RH. The passive NO isotope measurement technique provides an accurate method to determine variations in atmospheric δ N-NO values and a precise method for determining atmospheric δ O-NO values. The ability to measure NO isotopes over spatial gradients at the same temporal resolution provides a unique perspective on the extent and seasonality of fluctuations in atmospheric NO isotopic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Ambient NO 2 and/or NO x have also been collected for 15 N analysis using passive samplers (Smirnoff et al, 2012;Dahal and Hastings, 2016) or experimental actively-sampled cartridges (Savard et al, 2017) based on proprietary sampling media (Maxxam Analytics). When NO 2 isotopes have been collected for 15 N analysis and analyzed as nitrite in solution, it has been noted that an additional fractionation factor (~ +27.5 ‰) must be applied when using the denitrifier method to account for an additional oxidation to NO 3 − during bacterial processing (Casciotti et al, 2007;Dahal and Hastings, 2016;Coughlin et al, 2017).…”
Section: ) Advances In Field and Laboratory Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient NO 2 and/or NO x have also been collected for 15 N analysis using passive samplers (Smirnoff et al, 2012;Dahal and Hastings, 2016) or experimental actively-sampled cartridges (Savard et al, 2017) based on proprietary sampling media (Maxxam Analytics). When NO 2 isotopes have been collected for 15 N analysis and analyzed as nitrite in solution, it has been noted that an additional fractionation factor (~ +27.5 ‰) must be applied when using the denitrifier method to account for an additional oxidation to NO 3 − during bacterial processing (Casciotti et al, 2007;Dahal and Hastings, 2016;Coughlin et al, 2017).…”
Section: ) Advances In Field and Laboratory Methodologiesmentioning
confidence: 99%
“…Nitrogen dioxide (NO 2 ) for isotopic analysis has been captured using passive diffusion samplers that contain a quartz filter impregnated with TEA (Redling et al, 2013;Felix and Elliott, 2014;Dahal and Hastings, 2016). A recent study using control laboratory experiments determined precision and accuracy of passive NO 2 filters as a collection medium for isotopic analysis of δ 15 N and δ 18 O across varying environmental conditions (Coughlin et al, 2017). Another recent study collected δ 15 N and δ 18 O of NO 2 using an active sampling denuder assembly coated with a potassium hydroxide solution, guaiacol, and methanol solution .…”
Section: ) Advances In Field and Laboratory Methodologiesmentioning
confidence: 99%
“…These measurements were made using passive samplers (Ogawa pads; Ogawa USA, Pompano Beach, FL) that required soil chambers to be permanently closed, prohibiting integration with our automated chambers. The passive sampling pads are chemically pretreated so that they would collect either NO x , NO 2 , or NH 3 and have been demonstrated to work well under warm and humid conditions expected inside our soil chambers (Coughlin et al 2017). We did not detect NO 2 on the NO 2 pads, indicating any N accumulation on the NO x pads was mostly NO.…”
Section: Experimental Designmentioning
confidence: 99%
“…This technique is convenient in terms of time, portability, and cost of materials; however, it results in a much lower time resolution (i.e., weeks to months) compared to active sampling techniques (i.e., hours to days), and collections under low RH conditions have been reported to be not quantitative. Additionally, previous studies have indicated that passive samplers can yield systematic biases in isotopic compositions for molecules such as NO 2 · and ammonia (NH 3 ) that is caused by diffusion and postcollection artifacts such as isotopic exchange with water and/or loss of the analyte after collection. , …”
Section: Introductionmentioning
confidence: 99%